Reforming Teacher Education Something Old, Something New - Kirby, Sheila Nataraj (RAND Corporation, 2006)
Teachers for a New Era (TNE) is one of the latest efforts aimed at teacher education reform. Eleven institutions participate in TNE, which emphasizes evidence-based decisionmaking, collaboration between education and arts and sciences faculty, and teaching as an academically taught clinical-practice profession. The authors studied the 11 TNE sites to examine the process by which reform will result in highly qualified teachers capable of producing improvements in student learning.